Glycemic Control in Patients with Type 1 Diabetes: Comparison of Holidays versus Schooldays - Al Hayek, Ayman; Alwin Robert, Asirvatham; Almonea, Khuloud I.; Al Dawish, Mohamed Abdulaziz (Current Diabetes Reviews, 2024)
Background and Aims: To examine the influence of school life in children and adolescents with type 1 diabetes (T1D) by comparing the glycemic control and Ambulatory Glucose Profile (AGP) between the holidays and schooldays. Methods: This is a retrospective study conducted on 147 patients with T1D (14-19 years) who used an intermittently scanned Continuous Glucose Monitoring (isCGM) system to self-test their glucose levels during the periods of school time and holiday time. A record was maintained of the Continuous Glucose Monitoring (CGM) metrics i.e., Glucose Variability (GV) (%), mean Time in Range (TIR), Time above Range (TAR), Time below Range (TBR), and average time period of the hypoglycemic events during schooldays and the holidays. Results: The study revealed differences between the recorded values during the holidays and schooldays, in % in target 70-180 mg/dL (38.2 vs. 49.5; p = 0.039), mean glucose (194 vs. 185; p = 0.048), frequency of low glucose events (9.2 vs. 5.1; p = 0.036), mean duration of low glucose levels (117 vs. 65; p = 0.021), % TBR below 70 mg/dL (2.9 vs. 1.45; p = 0.023), % TBR below 54 mg/dL (1.1 vs. 0.51; p = 0.031), TAR 181-250 mg/dL (21.1 vs. 16.5; p = 0.037) and TAR >250 mg/dL (8.9 vs. 6.5; p = 0.043). On comparing the HbA1c levels of the study population recorded during the holidays (8.34%) with those recorded during the schooldays (8.13%), the HbA1c values during the school days were observed to be lower; however, no significant changes were noted in the HbA1c level between the holidays and schooldays. Concerning the FreeStyle Libre (FSL) scanning, the frequency during the holidays (n = 6.2) was significantly lower than during the schooldays (n = 9.5) (p = 0.042). Conclusion: From the findings, it appears that children with T1D have good diabetes control during schooldays rather than during the holidays. To improve their glucose control during the holidays, these patients may also benefit from receiving greater attention and guidance.
Keywords: Type 1 diabetes